ChIP‐Atlas: a data‐mining suite powered by full integration of public ChIP‐seq data. (9th November 2018) - Oki, Shinya; Ohta, Tazro; Shioi, Go; Hatanaka, Hideki; Ogasawara, Osamu; Okuda, Yoshihiro; Kawaji, Hideya; Nakaki, Ryo; Sese, Jun; Meno, Chikara
Abstract: We have fully integrated public chromatin chromatin immunoprecipitation sequencing (ChIP‐seq) and DNase‐seq data ( n > 70, 000) derived from six representative model organisms (human, mouse, rat, fruit fly, nematode, and budding yeast), and have devised a data‐mining platform—designated ChIP‐Atlas (http://chip-atlas.org ). ChIP‐Atlas is able to show alignment and peak‐call results for all public ChIP‐seq and DNase‐seq data archived in the NCBI Sequence Read Archive (SRA), which encompasses data derived from GEO, ArrayExpress, DDBJ, ENCODE, Roadmap Epigenomics, and the scientific literature. All peak‐call data are integrated to visualize multiple histone modifications and binding sites of transcriptional regulators (TRs) at given genomic loci. The integrated data can be further analyzed to show TR–gene and TR–TR interactions, as well as to examine enrichment of protein binding for given multiple genomic coordinates or gene names. ChIP‐Atlas is superior to other platforms in terms of data number and functionality for data mining across thousands of ChIP‐seq experiments, and it provides insight into gene regulatory networks and epigenetic mechanisms. Synopsis: ChIP‐Atlas (http://chip-atlas.org ) is an easy‐to‐use Web service for visualization and data mining of genome‐wide binding data for transcriptional regulators and modified histones that is based entirely on public ChIP‐seq data. This service allows: To browse protein binding at gene loci and genomic regions of interest. To identify potential target genes of and factors that colocalize with given transcriptional regulators. To search for proteins that are enriched at given sets of genes or genomic loci. Abstract : ChIP‐Atlas (http://chip-atlas.org ) is an easy‐to‐use Web service for visualization and data mining of genome‐wide binding data for transcriptional regulators and modified histones that is based entirely on public ChIP‐seq data.